FaST linear mixed models for genome-wide association studies - Lippert, Christoph; Listgarten, Jennifer; Liu, Ying; Kadie, Carl; Davidson, Bob; Heckerman, David (Nature Methods, 2011)
We describe factored spectrally transformed linear mixed models (FaST-LMM), an algorithm for genome-wide association studies (GWAS) that scales linearly with cohort size in both run time and memory use. On Wellcome Trust data for 15,000 individuals, FaST-LMM ran an order of magnitude faster than current efficient algorithms. Our algorithm can analyze data for 120,000 individuals in just a few hours, whereas current algorithms fail on data for even 20,000 individuals (http://mscompbio.codeplex.com/).